Effects of oxygen vacancy concentration and sintering temperature on rechargeable Li-ion storage performance of titanium niobate anode materials. Issue 4 (15th February 2023) - Kuo, Cheng-Kuan; Lin, Mei-Chun; Liu, Wei-Ren
Abstract: In this study, TiNb2 O7 (TNO) was prepared by a simple solvothermal method and subsequently high temperature sintering process as anode materials for Lithium-ion batteries (LIBs). The surface morphology and oxygen vacancies of as-prepared TNO were investigated by using different sintering temperatures from 700 o C to 1000 °C, namely TNO-700, TNO-800, TNO-900 and TNO-1000, respectively. The crystal structure, surface morphology as well as pore size distribution and oxygen vacancy content of a series of TNO anodes were characterized by X-ray diffraction (XRD), scanning electronic microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), surface area and pore analyzer (N2 adsorption/desorption isotherms), electron paramagnetic resonance spectrometer (EPR) and X-ray photoelectron spectrometer (XPS), respectively. The condition-optimized TNO-800 electrode exhibited brilliant rate capability and the highest reversible capacity which resulted from the micro-spherical structure and enough oxygen vacancies in terms of 246 mAh/g after 250 cycles and 248 mAh/g at 20C, respectively. The XPS analysis proved that samples in lower sintered temperatures had more oxygen vacancies from Ti/Nb peak shifting and integrated area ratio of the main peak to the shoulder peak in the O 1s spectrum. In addition, they also exhibited a stronger EFP signal than that of other samples at g = 1.99 which means the signal of paramagnetic oxygen vacancies. These results indicated that the porous structure and high specific surface area, as well as the existence of oxygen vacancies, play important roles in the electrochemical performance of TNO anode materials for LIBs. Hence, it is an effective manner to enhance the Li-ion storage applications for anode materials from this research. Graphical abstract: Image 1